Assessment of Energy-Efficient Building Details for Seismic Regions - Azinović, Boris; Kilar, Vojko; Koren, David (Springer Tracts in Civil Engineering,, 2022)
This open access book presents a methodology for the assessment of structural building details, taking into account the contemporary guidelines for earthquake-resistant and energy-efficient buildings. A review of structural details for energy-efficient buildings revealed that in some cases the structural system is interrupted, leading to solutions which are not suitable for earthquake-prone regions. Such typical examples would be the use of thermal insulation under the building foundation and reduction of the load-bearing elements' dimensions - also at the potential locations of plastic hinges which are crucial for the dissipation of seismic energy. The proposed methodology of assessment favours a collaboration of architects, engineers, contractors and investors in the early stage of building design. By this the methodology enables efficient decision-making and contributes to a selection of optimal building structural details. The book starts by presenting the typical structural details of the thermal envelope of energy-efficient buildings together with the scientific background required for understanding the process of detail development from all the relevant aspects. Over 20 examples of most frequent details are described and analysed to raise awareness of the importance of earthquake resistance, sustainability, energy-efficiency and thermal comfort for users.